Cultural Patterns and Gambling Law - Frańczuk, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The study focuses on the recent amendments to the Act of 19 November 2009 on gambling (Journal of Laws of 2009, No. 201, item 1540, as amended). Issues were discussed from both socio-cultural and legal perspectives. The socio-legal approach to gambling looks at the history of and present day gambling. In addition to reflections of a sociological nature, the paper focuses on the legal definition of gambling, the latest regulations governing it, and, above all, the shortcomings in the regulation of protective provisions, which may lead to hazards, especially among inexperienced players involved in online gambling. The benefits of liberalising online gambling regulations in some EU countries are also analysed. The paper examines the risks and benefits of gambling in terms of social, religious and legal norms, and also compares appropriate normative orders in that field. The final section suggests changes that should be made to the gambling act in order to protect players from becoming addicted to gambling.